Numerical and experimental investigation on water vortex power plant to recover the energy from industrial wastewater. (March 2023) - Edirisinghe, Dylan S.; Yang, Ho-Seong; Gunawardane, S.D.G.S.P.; Alkhabbaz, Ali; Tongphong, Watchara; Yoon, Min; Lee, Young-Ho
Abstract: Waste energy recovery is crucial to improving the overall energy efficiency of any industry. Industrial wastewater discharge contains a considerable amount of hydraulic energy, a waste that can recover using micro-hydropower concepts. Gravitational water vortex power (GWVP) is considered one of the most suitable micro-hydro extraction methods for such applications. Therefore, this study mainly focused on the numerical and experimental investigation of the GWVP plant, which was designed based on discharge water flow from an industrial fish farm located on the south coast of the Republic of Korea. The initial prototype model was investigated by simulations and experiments evaluating performance under three conditions: different rotational speeds, flow rates and water levels. The maximum hydraulic efficiency was recorded as 61.3% in simulation while 60.5% in the experiment for the prototype model. Then the actual scale simulation is also conducted to compare the performance with Froud similarity prediction. Actual scale simulation yields 6 kW of extracted power having 63.3% efficiency, whereas the deviation of efficiencies occurs due to the scaling effects. Thus, the flow field of each case was analysed considering the water-air interface, pressure contours and velocity vectors while justifying the variation of performance. Since the target power output was reached in the designed GWVP plant, an actual site application was proposed to recover the industrial waste energy as a sustainable solution. Highlights: Numerical and experimental investigation of vortex power plant. Energy recovery from industrial wastewater. Performance comparison between prototype and actual scale models. Flow analysis considering water-air interface, pressure and velocity. 61.3% maximum efficiency in simulation and 60.5% in experiment study.